An Empirical Analysis of Perceptual Judgments - Nicholas Ray (Baltic International Yearbook of Cognition, Logic and Communication, 2014)
This paper is a defense of Reformed Empiricism, especially against those critics who take Reformed Empiricism to be a viable account of empirical rationality only if it avails itself of certain rationalist assumptions that are inconsistent with empiricism. I argue against three broad types of criticism that are found in the current literature, and propose a way of characterising Gupta’s constraints for any model of experience as analytic of empiricism itself, avoiding the charge by some (e.g. McDowell, Berker, and Schafer) who think that the constraints are substantive.
Keywords: empirical rationality; reformed empiricism; perceptual judgements; epistemology; Anil Gupta